Exoplanets detection, formation, properties, habitability / John W. Mason (editor) - Mason, John (John W.) (Springer-Praxis books in astronomy and planetary sciences., 2008)
This edited, multi-author volume will be an invaluable introduction and reference to all key aspects in the field of exoplanet research. The reviews cover: Detection methods and properties of known exoplanets, Detection of extrasolar planets by gravitational microlensing. The formation and evolution of terrestrial planets in protoplanetary and debris disks. The brown dwarf-exoplanet connection. Formation, migration mechanisms and properties of hot Jupiters. Dynamics of multiple exoplanet systems. Doppler exoplanet surveys. Searching for exoplanets in the stellar graveyard. Formation and habita.